Susceptibility to Ventricular Arrhythmias Resulting from Mutations in FKBP1B, PXDNL, and SCN9A Evaluated in hiPSC Cardiomyocytes - Hector Barajas-Martinez; Maya Smith; Dan Hu; Robert J. Goodrow; Colleen Puleo; Can Hasdemir; Charles Antzelevitch; Ryan Pfeiffer; Jacqueline A. Treat; Jonathan M. Cordeiro (Stem Cells International)
Background. We report an inherited cardiac arrhythmia syndrome consisting of Brugada and Early Repolarization Syndrome associated with variants in SCN9A, PXDNL, and FKBP1B. The proband inherited the 3 mutations and exhibited palpitations and arrhythmia-mediated syncope, whereas the parents and sister, who carried one or two of the mutations, were asymptomatic. Methods and Results. We assessed the functional impact of these mutations in induced pluripotent stem cell cardiomyocytes (hiPSC-CMs) derived from the proband and an unaffected family member. Current and voltage clamp recordings, as well as confocal microscopy analysis of Ca2+ transients, were evaluated in hiPSC-CMs from the proband and compared these results with hiPSC-CMs from undiseased controls. Genetic analysis using next-generation DNA sequencing revealed heterozygous mutations in SCN9A, PXDNL, and FKBP1B in the proband. The proband displayed right bundle branch block and exhibited episodes of syncope. The father carried a mutation in FKBP1B, whereas the mother and sister carried the SCN9A mutation. None of the 3 family members screened developed cardiac events. Action potential recordings from control hiPSC-CM showed spontaneous activity and a low upstroke velocity. In contrast, the hiPSC-CM from the proband showed irregular spontaneous activity. Confocal microscopy of the hiPSC-CM of the proband revealed low fluorescence intensity Ca2+ transients that were episodic in nature. Patch-clamp measurements in hiPSC-CM showed no difference in INa but reduced ICa in the proband compared with control. Coexpression of PXDNL-R391Q with SCN5A-WT displayed lower INa density compared to PXDNL-WT. In addition, coexpression of PXDNL-R391Q with KCND3-WT displayed significantly higher Ito density compared to PXDNL-WT. Conclusion. SCN9A, PXDNL, and FKBP1B variants appeared to alter spontaneous activity in hiPSC-CM. Only the proband carrying all 3 mutations displayed the ERS/BrS phenotype, whereas one nor two mutations alone did not produce the clinical phenotype. Our results suggest a polygenic cause of the BrS/ERS arrhythmic phenotype due to mutations in these three gene variants caused a very significant loss of function of INa and ICa and gain of function of Ito.